Comunicação de más notícias na hemato-oncologia pediátrica: estratégias de profissionais de saúde - Oliveira, Suelen Gulart Portalette de (2024)
INTRODUCTION: Childhood cancer corresponds to a group of several diseases that have in common the uncontrolled regularity of abnormal cells and that can occur anywhere in the body. The expression “bad news” characterizes any and all messages notified to the patient or their family members that impact their future outlook in a negative sense. OBJECTIVES: Develop bad news communication strategies for children and adolescents with hemato-oncological disease and their families, together with professionals from the multidisciplinary team; Search for evidence in the literature about strategies for communicating bad news by professionals in the multidisciplinary team in pediatric hemato-oncology; Build strategies for communicating bad news together with professionals from the multidisciplinary team; Apply bad news communication strategies developed by professionals from the multidisciplinary team in pediatric hemato-oncology; Create a flowchart for communicating bad news between the team of pediatric hemato-oncology professionals and patients and family members. METHODOLOGY: This is a qualitative study, which was developed in a hemato-oncology unit, located in a municipality in the Central Region of Rio Grande do Sul. Data collection was carried out through a focus group, in the months of June, July and August 2023, with the participation of 23 professionals from the multidisciplinary team. The data were analyzed according to discursive textual analysis, which resulted in 107 units of meaning, originating 3 categories: communication in pediatric hemato-oncology is bad news; the family when faced with bad news; and strategies for communicating bad news in the context of pediatric hemato-oncology. The ethical aspects of research involving human beings were respected, obtaining approval from the Research Ethics Committee with the Certificate of Presentation for Ethical Appreciation number 68978923.5.0000.5346. RESULTS: The need to implement strategies aimed at communicating bad news in pediatric hemato-oncology was highlighted, including holding rounds twice a week, moments of discussing cases among the team, continued education with the team, playful strategies aimed at children, availability of a private and welcoming space, complete registration and free access to the system by all team professionals and the creation of a flowchart to guide the team in the process of communicating bad news. FINAL CONSIDERATIONS: The strategies for communicating bad news listed by study participants include adequate, private and welcoming space, clear and objective language, emotional and empathetic reception, and continued education with the entire team. Furthermore, they suggest using the flowchart for the process of communicating bad news.